2010
DOI: 10.4103/0972-9941.65163
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of patients of gastroesophageal reflux disease treated with laparoscopic Nissen′s fundoplication

Abstract: AIMS:To evaluate retrospectively the outcome of laparoscopic fundoplication in a cohort of patients with typical symptoms of gastroesophageal reflux disease (GERD).MATERIALS AND METHODS:Forty-two patients with typical symptoms of GERD, who were operated for laparoscopic Nissen's fundoplication from March 2001 to August 2008, were studied. The study was limited to patients with positive findings on upper gastrointestinal (GI) endoscopy done by us and "typical" symptoms (heartburn, regurgitation, and dysphagia) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…The majority of reports originated in Europe (n = 83) and North America (n = 55) [121,. The remaining series originated in Australia or New Zealand (n = 11) [290][291][292][293][294][295][296][297][298][299][300], Asia (n = 8) [301][302][303][304][305][306][307][308], Africa or the Arab peninsula (n = 3) [309][310][311] or South America (n = 2) [312,313]. Overall, the case series reported a male predominance with women accounting for 46.2 ± 0.9% (range: 30.3-91.0%; P < 0.01) of the patients.…”
Section: Sex and Fundoplicationmentioning
confidence: 99%
“…The majority of reports originated in Europe (n = 83) and North America (n = 55) [121,. The remaining series originated in Australia or New Zealand (n = 11) [290][291][292][293][294][295][296][297][298][299][300], Asia (n = 8) [301][302][303][304][305][306][307][308], Africa or the Arab peninsula (n = 3) [309][310][311] or South America (n = 2) [312,313]. Overall, the case series reported a male predominance with women accounting for 46.2 ± 0.9% (range: 30.3-91.0%; P < 0.01) of the patients.…”
Section: Sex and Fundoplicationmentioning
confidence: 99%
“…They had also found that gastroesophageal reflux disease had equal sex distribution (50% for males and females) [ 3 ]. Nagpal et al [ 4 ] found that 57.14% of the patients were males and 42.86% were females [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Angina like chest pain and respiratory symptoms (cough and hoarseness) were not seen ( Table 1 ). In the study done by Nagpal et al [ 4 ], the most common symptom was heartburn, followed by regurgitation and constipation [ 4 ]. In a study of 107 patients done by Balsara et al [ 6 ], the symptoms on presentation were heartburn in all (100%), regurgitation in 43 (50.59%), and volume reflux in 39 (45.88%) patients [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…La définition de l'échec n'est pas clairement établie et reste peu consensuelle. La récidive du pyrosis et des régurgitations peuvent survenir dans 10 % à 18 % des cas dans les 5 à10 ans post-opératoires 80,81 . Une récente étude suédoise ayant colligé 2.655 patients ayant eu une chirurgie laparoscopique anti-reflux avec un suivi de 5,1 années montrait un taux de récidive de 17,7 %.…”
Section: Echecs : Recours Au Traitement Médical Ou Ré-interventionunclassified